Наративна стратегія повісті Ю. Шкрумеляка «Огні з полонин» як авторський інваріант декодування «гуцульського тексту» перших десятиліть ХХ століття - Бикова, Тетяна; Bykova, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2015)
На матеріалі літературознавчого аналізу «гуцульського» тексту Ю. Шкрумеляка розкрито авторське втілення майбутнього у вигляді часопросторового фантастичного передбачення відродження Гуцульщини. Текст твору представлений як своєрідна квазіісторія краю, оспівана в художній формі. Такий аспект викладу матеріалу дає змогу спрямувати думку читача щодо певних варіантів утілення майбутнього в реальних подіях.On the material of literary analysis «Hutsul» text Yu. Shkrumelyak disclosed embodiment future of copyright in a fantastic time and spatial prediction revival of Hutsul. The text of the work presented as a kind kvazihistory edge, glorified in artistic form. The writer seeks to show the formation of views on the «new» Hutsul not only real historical figures and characters, and, in fact, argues that surreal world and the natural world, suffering from social injustice, joins the desire to «clean» the land of evil. Author kvazihistory the exceptional mission Hutsulshchyna autochthon genius, made the principles of the author's original game with the reader, the text of which is an intermediary between the two entities that receive certain information from reading. This aspect of the presentation of the material makes it possible to direct the reader according to certain embodiments the future of real events.
Narrative Strategy Novel Yu. Shkrumelyak «Lights From the Valley» as the Author Invariant Decoding «Hutsul text» First Decades of the XX Century
Keywords: Гуцульщина як текст; наративна стратегія; квазіісторія; гуцульський текст; наратор; Hutsulshchyna as text; narrative strategy; kvazihistory; Hutsul text narrator